Perilaku Petani dalam Pembayaran Zakat Hasil Pertanian di Desa Labuhan Kuris Kecamatan Lape Kabupaten Sumbawa - Bobi Arisandi; Titiek Herwanti; Moh. Huzaini (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2019)
This study aims to find out how the behavior of farmers in payment of zakat for agricultural products in Labuhan Kuris Village Lape District Sumbawa Regency. This study uses qualitative methods. The results of this study are: (1) Behavior farmers in paying zakat for agriculture in Labuhan Kuris Village District Lape Sumbawa Regency which tends to follow the customs or habits of grandmothers his ancestors, namely giving alms to the desired people, they are also assume that if it produces a harvest of about 10 sacks the zakat issued about 1 sack, they do not prioritize calculations with the size of a kilogram even though each sack is produced from the harvest The kilograms are not necessarily the same. (2) Communities in Labuhan Kuris Village Lape District Sumbawa Regency in general does not yet understand the meaning of agricultural zakat as a whole, only some Muslims in Labuhan Kuris village know that the zakat law is an obligation that must be fulfilled. In the form of distribution of community agricultural zakat in Labuhan Kuris Village Lape District Sumbawa Regency is generally only in the form of donations, infaq or alms done directly without intermediaries. (3) Community in the Village Labuhan Kuris, Lape Subdistrict, Sumbawa Regency, performs zakat agriculture is given directly to the needy, poor or elderly people who are around the neighborhood and also to their own relatives or relatives.